N'Dama cattle underestimated - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1987)
Initial results from a study of N'Dama cattle in Gambia show that this trypanotolerant breed's potential as a milk producer has long been underestimated. The results indicate that they can produce over 265 kg of milk for domestic consumption as...